Cycling into Headwinds: Analyzing Practices That Inhibit Sustainability. (November 2018) - Scheurenbrand, Klara; Parsons, Elizabeth; Cappellini, Benedetta; Patterson, Anthony
Using the example of cycling, the authors contribute to public policy debates surrounding sustainability. They employ practice theory to shift the debate away from consumer choice and agency to examine instead why sustainable practices are not always available to consumers. Therefore, rather than asking, "Why don't people cycle?" the authors ask, "Why isn't the practice of cycling thriving?" Practice theory focuses on material, meanings, and competences as the components of a practice, positing that a practice can thrive and grow only when these elements come together. By looking at how practices compete for the same set of elements, the authors demonstrate how some practices (e.g. driving, schooling, policing) come to dominate or inhibit others (i.e., cycling). In terms of the theme of this special issue, then, instead of excavating anticonsumption as a precursor to practices (i.e., a choice not to engage in those practices), by unpacking practices, the authors examine the mechanisms through which this choice is restricted.